FORMULASI DAN UJI STABILITAS FISIK SEDIAAN SERUM DARI ESKTRAK BUAH MENTIMUN (Cucumis Sativus L.) SEBAGAI ANTIOKSIDAN - Ratnasari, Nuryati; Jenta Puspariki; Farhan; Puspariki, Jenta (Sekolah Tinggi Ilmu Kesehatan Holistik, 2023)
Background: Serum is a preparation with high concentration of active substance and low viscosity which gives a more comfortable effect and spreads easily on the skin surface. Cucumber is a member of the cucurbitaceae family and can be a source of natural antioksidants because it contains vitamin C and flavonoids which are free to break free radikcal reactions and can restore electrons to unstable cells. Objective: This study aims ti determine the formulation of cucumber extrack in the form of facial serum and to determine the stability of cucumber extrack serum through organoleptic tests, gomogeneity tests, pH tests, and dispersibility tests. Methods: This study uses an action reseach design (action reseach) and uses the concept according to Kurt Lewin which consists of 4 components namely planning, action, observation, and reflection. Serum preparations are made with the main ingredients of cucumber (Cucumis Sativus L.), xhantan gum methyl paraben, butylene glycol, and aquadest with different concetrations of preservatives. Results: The results of the organoleptic test for 21 days of serum preparation with storage at room temperature, the positive control and F1 resulted in a preparation with good stability, and the negative control and F2 there was a change in aroma, shape and fungus began to appear on the 6th day. Conclusion: The serum preparation is relatively stable during the storage is the first formula with a pH of 6,69 above the standard pH (4,5-6,5) which is not safe for skin use.